Larval morphology of genus Lancetes (Coleoptera: Adephaga: Dytiscidae): The hypothesis of sister-group relationship with the subfamily Dytiscinae revisited - Alarie, Yves (2002)
Descriptions of the larvae of Lancetes angusticollis (Curtis), L. lanceolatus (Clark), L. subseriatus Zimmermann, L. flavoscutatus Enderlein, L. delkeskampi Ríha, and L nigriceps (Erichson) are provided. Characters from larval morphology are analyzed to infer the phylogenetic relationships of the genus Lancetes Sharp with other genera of Dytiscidae. A parsimony analysis based on 51 informative larval characteristics was conducted with the program NONA. The most parsimonious tree supports a sister-group relationship between the genus Lancetes and members of the subfamily Dytiscinae. The only unambiguous synapomorphy in support of this hypothesis is the secondary subdivision of some cephalic appendages. Other putative synapomorphies are the proximal articulation of the primary seta CO7 both on meso- and meta-coxa and the presence of additional primary setae on the ventral margin of the tibiae. Based on several character states including the presence of multifragmented urogomphi, the genus Lancetes is monophyletic.